TINJAUAN TEOLOGIS TENTANG PERCERAIAN MENURUT INJIL MATIUS 19:1-9 BAGI UMAT KRISTIANI DI INDONESIA - Grady Aditya; Sapto Hariadi (Sekolah Tinggi Teologi Duta Panisal, 2022)
The Gospel of Matthew 19:1-9 is one of the Bible passages that has the same reality as the Indonesian reality, where there is tension between marriage and divorce. This passage from Matthew 19:1-9 is famous as a text that explains the prohibition of divorce. The text of Matthew 19:1-9 implies a paradox in it, because on the one hand marriage is a union from God which cannot be divorced at all, but on the other hand divorce can be done with an exception. The problem in Christianity is that this passage is often used to prohibit divorce for any reason. So this indirectly affects Christian theology of marriage, because of the tension that prohibits divorce for the sake of marriage from God. But what actually happens is that divorce still exists and can be done with an exception. This study uses a qualitative method. Data were collected by interview technique. Respondents in this study were 6 peoples consisting of lay congregations and God's servants (pastors). The number of questions given by the researcher to each respondent, amounted to 7 questions. The results showed that there were some who supported divorce and those who did not support it.